Overview of Anemia among Systemic Lupus Erythematosus Patients in Reproductive Age Women based on Reticulocyte Hemoglobin Equivalent (RET-He) Level and Reticulocyte Count - Ismiana Fatimah Modjaningrat; Amaylia Oehadian; Mohammad Ghozali; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2017)
Background: Anemia is a common manifestation found among patients with Systemic Lupus Erythematosus (SLE). It may be caused by iron-deficiency, autoimmune hemolytic, and chronic inflammation. Each anemia has different therapy approachments. Without adequatemanagement, anemia may lead to poor prognosis. By identifying the etiology of anemia, appropriate management could be conducted. Reticulocyte Hemoglobin Equivalent (RET-He) and reticulocyte count test may distinguish anemia based on its etiology. This study aimed to give scientific portrayed of the proportion of anemia based on its etiology among patients with SLE using RET-He and reticulocyte count.Method: This study involved women diagnosed with SLE underwent outpatient treatment in Rheumatology Clinic, Dr. Hasan Sadikin General Hospital during SeptemberOctober 2016. Data were collected from blood exam using 35-parameters hematology Sysmex by calculating levels of hemoglobin, RET-He, and reticulocyte count.Results: Seventy four female patients were volunteered as subject in this study with median of age was 29.5 (16-70) years old. Thirty four (46%) of 74 subjects weresuffering from anemia and 12 (35%) of them were between 25-34 years old. Proportion of iron-deficiency anemia, autoimmune hemolytic anemia, and chronic inflammatory anemia were 14 ( 41%), 13 (38%), and 7 (21%), respectively.Conclusion: Based on hemoglobin, RET-He, and reticulocyte count, iron-deficiency anemia is the most common anemia among patients with SLE in repoductive age.Keyword: Age, Anemia, Reticulocyte, RET-He, Systemic Lupus Erythematosus (SLE)